Effects of Job Stress on Job Performance in Nepali Commercial Banks - Basnet, Dinesh; Gwachha, Anju; Poudel, Nira Devi (Management Dynamics, 2022)
Stress is an unavoidable and unenviable issue people encounter in their professional and personal lives. More specifically, in a banking professional’s life, due to changing demands of work and working conditions, bankers experience work stress these days. The present study was carried out to examine how work-related stress affects workers’ performance on the job. The survey was conducted by administering the structured questionnaire to different categories and levels of bankers working in various banks in Kathmandu valley. Statistical tools such as descriptive statistics, correlation, and regression were used to examine the collected data. The study revealed a weak negative link between role ambiguity and job performance and demonstrated no connection between workload and role conflict and Job performance. The result suggests that a medium level of workload and role conflict have a favorable impact on job performance. This indicates that workplace stress is not always harmful but has a positive influence on performance. The finding and suggestions of this study might help commercial banks to mitigate the stress level of the employees.